Teacher educators as curriculum developers: a case study of teacher education colleges in Cambodia - Tep, Vandy (Frontiers in Education, 2024)
This case study explored the actual practices, challenges, and strategies employed by 25 teacher educators as curriculum developers, based on an analysis of documents and interview data. The research framework was grounded in curriculum innovation, drawing from both literature review and practical insights. The results revealed that teacher educators were highly aware of their roles as curriculum developers, offering specific activities for syllabus development and revision, schemes of work and lesson plans, teaching practice, and assessment. However, challenges persist in terms of curriculum developers' knowledge base, timeframes, and professional development, particularly within the Cambodian context. Professionally, teacher educators overcame these challenges in various ways, most notably through autonomy in improving syllabus content and teaching flexibility, as well as through formal training and informal learning from and with their colleagues and student teachers in the workplace. The study contends that practitioners' innovation and flexibility in using and developing syllabi in practice are more robust than following prescribed curriculum frameworks and instructions. This study addresses a gap in the literature regarding the role of teacher educators in curriculum development and has implications for improving educational practice, research, and policymaking in the field. Further research should investigate the influence of teacher educators' professional roles as researchers and curriculum developers on improving teacher education programs.